Po POLITIK ISLAM DAN ISLAMISASI DI LAMPUNG: JEJAK KESULTANAN BANTEN DALAM STRUKTUR SOSIAL DAN KEAGAMAAN - Aris Munandar (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
This research examines the political role of the Banten Sultanate in the Islamisation process in Lampung and its impact on the social and religious structure of the local community. Islamisation in Lampung did not only occur through da'wah, but also through political and economic channels, especially through the pepper trade that established a close relationship between Lampung and Banten. The Sultanate of Banten played a strategic role in strengthening the teachings of Islam by sending ulama, building mosques, and influencing the legal system and local leadership. This research uses the library research method by analysing historical sources, academic journals, and relevant documents. The results show that the Islamic politics of the Banten Sultanate contributed to integrating Islam into Lampung's social and customary systems. The customary leadership structure underwent modification with the increasing role of ulama in decision-making, as well as the integration of Islamic law in customary norms. Islamisation also occurred through cultural acculturation, where local traditions began to be adapted to Islamic values. Islamisation in Lampung is thus not only a religious process, but also a political phenomenon that shapes the social identity of the community to this day.